PENGARUH LINGKUNGAN KERJA, FAKTOR PSIKOLOGIS DAN KETERAMPILAN TERHADAP KINERJA PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI KALIMANTAN BARAT - B11211124, SRI MINARNI (Universitas Tanjungpura, 2014)
The success of an organization is depend on the performance of human resources that directly or indirectly contribute to the organization. To obtain optimal performance of the existence of human resource in the organization, then the organization needs to know the factors that can influence the development of human resources. Here we need the development program of human resource management in view of the work environment factors, psychological and skills so that an increase in skills, knowledge and talents of employees of Industry and Trade of the Province of West Kalimantan in a holistic and sustainable. The purpose of this research was to determine the effect of the work environment, and psychological factors on the performance skills of employees at the Department of Industry and Trade of the Province of West Kalimantan. The method used in this study is a design method of associative or causal. Sampling method in this study using the Stratified Random Sampling (SRS) that populations grouped into strata based on the unit of West Kalimantan Provincial Office of Industry, UPSMB, Pontianak Metrology UP, UP and UP-Metrology Singkawang IKM where the overall number of samples as many as 41 people. Data processing using Multiple linear regression analysis. The results showed that the value of the coefficient of determination of 0.285 so it can be concluded that the influence of the work environment variables, psychological factors and skills to fluctuations in the value or performance variable variation is equal to 28.5% and by 71.50% influenced by other variables besides variables in this study. Variables simultaneously work environment, psychological factors and skills significantly affect the performance of the employee at the Department of Industry and Trade of the Province of West Kalimantan. Of the partial test results can be concluded factors skill no significantly affect to the performance of the empolyee, while the variable work environment and psychological factors significantly affect the performance of the empoyee at the Department of Industry and Trade of the Province of West Kalimantan. Keywords: Work Environment, Psychological Factors, Skills, Performance